ANALISIS KENDALA PEMBELAJARAN MATEMATIKA SISWA KELAS VI SDN KEDAUNG KALIANGKE 09 PETANG - Sholikha, Alifia Najma (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2024)
This research investigates the learning difficulties faced by sixth-grade students at SDN Kedaung Kaliangke 09 Petang in terms of mathematics. This difficulty arises because students perceive mathematics as a difficult subject. The purpose of this research is to identify the learning difficulties and factors influencing these difficulties among sixth-grade students. This research employs a qualitative descriptive method with 17 sixth-grade students at SDN Kedaung Kaliangke 09 Petang and their teachers as subjects. Data collection techniques include observation, interviews, and documentation studies. The data is analyzed using the Miles and Huberman data analysis model. The analysis results show that students experience difficulties in several aspects, including reading and understanding the meaning of questions, understanding concepts, using formulas, and process skills. Factors influencing these difficulties include internal factors such as student attitudes, intelligence, motivation, and interest, as well as external factors such as the teacher's teaching methods, learning media, school facilities and class hours, learning history, and family conditions.